Fluoroquinolone-Mediated Tendinopathy and Tendon Rupture - Ezgi Duman; Sigrid Müller-Deubert; Girish Pattappa; Ioannis Stratos; Stephan A. Sieber; Hauke Clausen-Schaumann; Victoria Sarafian; Chisa Shukunami; Maximilian Rudert; Denitsa Docheva (Pharmaceuticals)
The fluoroquinolone (FQ) class of antibiotics includes the world’s most prescribed antibiotics such as ciprofloxacin, levofloxacin, and ofloxacin that are known for their low bacterial resistance. This is despite their potential to trigger severe side effects, such as myopathy, hearing loss, tendinopathy, and tendon rupture. Thus, healthcare organizations around the world have recommended limiting the prescription of FQs. Tendinopathy is a common name for maladies that cause pain and degeneration in the tendon tissue, which can result in tendon rupture. Whilst there are several identified effects of FQ on tendons, the exact molecular mechanisms behind FQ-mediated tendon rupture are unclear. Previous research studies indicated that FQ-mediated tendinopathy and tendon rupture can be induced by changes in gene expression, metabolism, and function of tendon resident cells, thus leading to alterations in the extracellular matrix. Hence, this review begins with an update on FQs, their mode of action, and their known side effects, as well as summary information on tendon tissue structure and cellular content. Next, how FQs affect the tendon tissue and trigger tendinopathy and tendon rupture is explored in detail. Lastly, possible preventative measures and promising areas for future research are also discussed. Specifically, follow-up studies should focus on understanding the FQ-mediated tendon changes in a more complex manner and integrating in vitro with in vivo models. With respect to in vitro systems, the field should move towards three-dimensional models that reflect the cellular diversity found in the tissue.